To Study the Correlation of Levels of Inflammatory Markers with the Duration of Treatment in Patients Diagnosed with Pulmonary Tuberculosis: A Longitudinal Study - Vedant Dilip Zalke; Anil Sontakke; Sagar Kolte; Ali Dhuru; Hassan Ali; Satyam Mahakale; Vatsal Sanjaybhai Jetani (Annals of African Medicine, 2026)
Abstract Background: Pulmonary tuberculosis (PTB) is characterized by systemic inflammation, which influences disease severity and treatment response. Conventional tools such as sputum microscopy and chest radiography have limitations in dynamically reflecting inflammatory activity during therapy. This study aimed to evaluate the relationship between inflammatory marker levels and duration of antitubercular treatment and to assess their correlation with radiological severity. Materials and Methods: This longitudinal observational study was conducted at a tertiary care hospital and included 50 adults newly diagnosed with PTB. All patients received standard first-line antitubercular therapy as per the National Tuberculosis Elimination Programme. Inflammatory markers, such as erythrocyte sedimentation rate (ESR), C-reactive protein/high-sensitivity CRP (CRP/hsCRP), neutrophil–lymphocyte ratio (NLR), total leukocyte count (TLC), and red cell distribution width (RDW), were measured at baseline, end of the intensive phase, and end of treatment. Radiological severity was assessed using a modified chest X-ray scoring system. Repeated-measures and correlation analyses were performed. Results: All inflammatory markers were significantly elevated at diagnosis and showed a progressive, statistically significant decline with treatment. By treatment completion, normalization was observed in ESR (96%), TLC (100%), CRP/hsCRP (76%), NLR (60%), and RDW (92%). Higher marker levels correlated with greater radiological severity, while normalization was associated with radiographic improvement, though residual changes persisted in some patients. Conclusion: Serial inflammatory markers closely reflect disease activity and therapeutic response in PTB. Their combined use with clinical assessment and chest radiography offers a simple, cost-effective adjunct for treatment monitoring, particularly in resource-limited settings.